Field applications of exogenous hormones- Gonadotropin and Prostaglandin - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1986)
prostaglandin F2α(PGF) and gonadotropin-releasing hormone (GnRH) have provided new dimensions in resolving certain reproductive maladies. Effective when used properly, these hormones have the advantage of mimicking the physiological activity of natural hormones without the negative, overriding effects of synthetic products. Effective use of the hormones requires accurate diagnoses. Moreover, side effects are nil except when PGF is mistakenly administered to pregnant animals. The effect of PGF in humans must be recognized. Current research under way gives promise that GnRH may have beneficial effects in the early postpartum cow suffering from problems around the time of calving.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Exogenous hormones; Gonadotropin; Prostaglandin F2-α